The role of Kurdsat TV in preserving identity and Kurdish Society Culture - Mohammed, Asst.L. Sarkawt Ahmed; Hawija, Asst.L. Khanda Saifuddin (Sulaimani Journal for Humanities, 2025)
This research entitled (The role of Kurdsat Satellite TV in preserving the identity and culture of the Kurdish society) similar to any other researchs comprises scientific steps to reach the information that attracted its researcher’s attention. The first step begins with the issue: (to what extent does Kurdsat Satellite TV participates in preserving and promoting the Kurdish society’s identity, culture and values?) which is aimed to realize the role of Kurdsat Satellite TV in paying attention to preserve the identity and cultural survival of the Kurdish society. Studying the media arena that Kurdsat Satellite TV has devoted to preserving and maintaining the society’s identity, culture and value. The research is based on descriptive analytical method and intentionally targets the TV’s programs of March, 2024 as a sample. The most preeminent conclusion reached by the researchers is: (All Kurdsat Satellite TV programs serve the Kurdish culture and identity and tries hard to preserve the Kurdish culture. In all programs, some of the units of the research’s tables exist in the programs and you wouldn’t find any program does not include Kurdish contents. Kurdsat Satellite TV has specific programs aimed to preserving the Kurdish culture and identity, which are the programs: (Kurdsat Kurdawary) and (Naway Rozhhelat) which have the most components of Kurdish identity and culture, and their viewers get the Kurdish culture and identity’s messages easily. The researchers’ most important suggestions and recommendations are reflected in these points: The presenters of the Kurdish TV’s that interested in preserving Kurdish identity and culture are obliged to wear Kurdish costumes and speak fluent Kurdish. Kurdsat Satellite TV to continue these two programs: (Kurdsat Kurdawary) and (Naway Rozhhelat), and try to do similar programs. Conducting researches on reclaiming the different regional identities and cultures in Kurdistan to reinforce a shared national identity. Pay attention to researches that enhances media content and identifying the strengths and weaknesses of the media in terms of taking into consideration or neglecting the Kurdish national identity.
Keywords: Role; Kurdsat Channel; Identity; Culture